The Regulatory NOD-Like Receptor NLRC5 Promotes Ganglion Cell Death in Ischemic Retinopathy by Inducing Microglial Pyroptosis - Deng, Yang; Fu, Yunzhao; Sheng, Longxiang; Hu, Yixin; Su, Lishi; Luo, Jiawen; Yan, Chun; Chi, Wei (Frontiers in Cell and Developmental Biology, 2021)
Retinal ischemia is a common pathological event that can result in retinal ganglion cell (RGC) death and irreversible vision loss. The pathogenic mechanisms linking retinal ischemia to RGC loss and visual deficits are uncertain, which has greatly hampered the development of effective treatments. It is increasingly recognized that pyroptosis of microglia contributes to the indirect inflammatory death of RGCs. In this study, we report a regulatory NOD-like receptor, NOD-, LRR- and CARD-containing 5 (NLRC5), as a key regulator on microglial pyroptosis and the retinal ischemia process. Through an in-depth analysis of our recently published transcriptome data, we found that NLRC5 was significantly up-regulated in retina during ischemia–reperfusion injury, which were further confirmed by subsequent detection of mRNA and protein level. We further found that NLRC5 was upregulated in retinal microglia during ischemia, while NLRC5 knockdown significantly ameliorated retinal ischemic damage and RGC death. Mechanistically, we revealed that knockdown of NLRC5 markedly suppressed gasdermin D (GSDMD) cleavage and activation of interleukin-1β (IL-1β) and caspase-3, indicating that NLRC5 promotes both microglial pyroptosis and apoptosis. Notably, we found that NLRC5 directly bound to NLRP3 and NLRC4 in inflammasomes to cooperatively drive microglial pyroptosis and apoptosis mediating retinal ischemic damage. Overall, these findings reveal a previously unidentified key contribution of NLRC5 signaling to microglial pyroptosis under ischemia or hypoxia conditions. This NLRC5-dependent pathway may be a novel therapeutic target for treatment of ischemic retinopathy.